"Oh boy, I ain't playin' no games!": making sense with youth in the aural imaginary. Issue 3 (14th May 2020) - Petchauer, Emery
Abstract : Purpose: This paper aims to explore how sounds and attunements to particular organizations of sound collide across an English language community learning space. The activities in the paper come from a six-week summer initiative that connected middle school youth with community artists for writing songs and rap lyrics, making beats and hip-hop DJing. Design/methodology/approach: This paper draws from the interdisciplinary field of sound studies and, specifically, the concept of aural imaginary to explore the collisions alive and in-motion across the learning space. The paper uses qualitative and ethnographic approaches to explore the research questions. Findings: The findings focus on how youth hear certain sounds and organizations of sound in music as "old" and "new, " and how these shifting listening entangle talk, claims and interactions in the learning space. The findings also trace the ways that youth use sound as an active, aural resource to make competing distinctions between rapping, singing and talking. Originality/value: This paper reasserts the role of sound in multiliteracies, hip-hop and English education work, keying into the ways it collides with other aspect of the learning space. The paper raises questions about what educators might attune themselves to by considering English education as already taking place in a youth aural imaginary.